Des bienfaits de la nature aux services écosystémiques - Georges Serpantié; Philippe Méral; Cécile Bidaud (VertigO, 2012)
This article replaces the rising concept of "ecosystem service" (ES) in the western history, by bringing to light the continuities, the oppositions and the breaks which accompanied the genesis of this concept or its former equivalents. A “friendly nature”, the existence of "benefits", "the services" and "the utilities" were ideas regularly emphasised, but for different reasons, for the philosophers of the Antiquity, the naturalists of the Ancien Régime, the romantic poets, the engineers in search of credits or of incentive laws for the afforestation, and henceforth, the scientific ecology. The study leans on the case of the forest, the most evoked ecosystem regarding ES. Some properties of this concept, that may be due to its history, are discussed: its ambiguities, its mutations and its asymmetry, but also the contradictions that arise from its practical use in local designs.